A multi-method case study of textile craft-design applications – usability and effects on the design process. Issue 2 (1st October 2018) - Sini, Riikonen; Pirita, Seitamaa-Hakkarainen
This article presents a multi-method case study of five mobile device and desktop computer applications intended specifically for craft-design. The main aim of the study was to investigate the effects of application usage on the craft-design process and to analyse the usability of the applications from three perspectives: user experience, traditional usability and functionality. Eight master's level craft teacher students evaluated the applications and used those to conduct a design task on a Virtual Design Studio course at the University of Helsinki. To enable an authentic working environment and style for the participants and to gather research data remotely, a multi-method approach was designed that included data from questionnaires, written tasks and recordings of screen events. Analysis of the effects of application usage on the craft-design process revealed three factors that promote changes: the usability of an application, new possibilities and limitations compared to traditional design methods and the technical expertise of the designer – usability being the most significant factor behind the changes observed.